Simulation of A Hot-rolled H-section Steel Beam Subject to Static Loading Based on Discrete Element Method. (2017) - Zhou, Li-Qiang; Yang, Bo
Abstract: In this paper, a new discrete element method (DEM) containing particle flow code (PFC) is presented as an efficient-to-implement alternative to the existing finite element method (FEM) for simulating internal forces and deformations of a hot-rolled H-section steel beam subject to static loading. Unlike FEM, which is efficient to solve continuous problems, the PFC method can solve discontinuous problems, such as collapse procedure of structures, and the collapse procedure of the structure can be monitored at different times in a more time-saving way. First of all, a linear constitutive model in FEM was built to compare with the linear parallel bond model built in PFC, a hot-rolled H-section steel beam considering geometrically non-linearity subject to static loading was simulated and the simulation results were compared with theoretical solution and FEM results. Both internal forces and deformations before yielding were compared and good agreements were achieved. Secondly, with the object-oriented programming technique and the redeveloped interface of PFC, a user-defined parallel bond model was developed to consider material nonlinearity and compared with the bilinear constitutive model built in FEM. Both internal forces and deformations before and after yielding were compared and good agreements were observed. Thus, the DEM model adopted in this paper can be efficiently used to simulate the behavior of the H-section steel beam. In the future, the developed parallel bond model can be used to simulate the performance of H-section steel beam subject to vertical impact loading and three-dimensional steel framed structure subject to horizontal collision.